Using Human Resource Index (HRI) to Analyze Employee Satisfaction, Perceived Organizational Support, and the Impact on Quality of Management and Organization Effectiveness (A Study in Indonesian Manufacturing Companies) - Priatna, Angka; Hadiyat, Yayan; Indrawati, Nina Sri; Manaf, Chaeruddin (Journal of Social Transformation and Regional Development, 2025)
This study examines the impact of Perceived Organizational Support (POS) on employee satisfaction, quality of management, and organizational effectiveness by using HRI attributes to construct the research variables. The research employs a quantitative cross-sectional survey design. A proportionate stratified random sampling technique was used to select a sample of 241 respondents from a population of 415 employees. Data collection was conducted using structured questionnaires, and data analysis included descriptive statistics to measure the Human Resource Index (HRI) and research variables using SPSS 27. Inferential statistical analysis involved measurement model testing and structural path analysis via Partial Least Squares Structural Equation Modeling (SEM-PLS) using WarpPLS 7.0. Findings indicate that POS has a very strong and significant positive effect on employee satisfaction, as well as a moderate but significant positive influence on organizational effectiveness. Employee satisfaction plays a crucial role in improving both management quality and organizational effectiveness directly. Despite the presence of organizational support, employee perceptions of human resource management (HRM) practices remain moderate, with a Human Resource Index (HRI) average score of 3.23, suggesting HRM practices are positive yet not fully optimized. Certain HRI attributes—such as reward systems, employee participation, and organizational concern for employees—show relatively low scores and represent areas needing improvement. Addressing these aspects is vital to reinforce the role of POS in enhancing employee satisfaction, thereby elevating management quality and organizational effectiveness. The study highlights that strategies focusing on tangible organizational support, continuous reward and recognition systems, enhanced employee participation, and improved management quality must be prioritized to foster a more productive work environment, higher employee satisfaction, and more efficient and effective organizations.